2017
DOI: 10.1108/ijccsm-01-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and adaptation to climate change in Malaysian real estate

Abstract: Purpose There is a growing concern in recent years regarding climate change risks to real estate in the developed and developing countries. It is anticipated that the property sector could be affected by variable climate and related extremes as well as by the strategies adopted to combat greenhouse gas (GHG) emissions. This paper aims to analyse the current knowledge regarding future climate changes to understand their possible impacts on the real estate sector of Malaysia with an aim to help stakeholders to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…However, application of joint analysis of flood variables is still very limited for flood analysis in Malaysia. Increasing risk of flood in recent years has posed a major challenge in the Malaysian development [14], [15]. A number of recent studies revealed increasing frequency and severity of rainfall extremes in peninsular Malaysia [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, application of joint analysis of flood variables is still very limited for flood analysis in Malaysia. Increasing risk of flood in recent years has posed a major challenge in the Malaysian development [14], [15]. A number of recent studies revealed increasing frequency and severity of rainfall extremes in peninsular Malaysia [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…The general characteristics of the rivers are summarized in Table 1. The area is located near the equator, with a tropical climate characterised by uniformly high temperatures, high humidity and abundant rainfall [27]. It has an average annual rainfall of 2300 mm and a mean daily temperature between 21 °C and 32 °C [28].…”
Section: Introductionmentioning
confidence: 99%
“…Sejak tahun 1951, suhu permukaan di Malaysia meningkat sebanyak 0.18°C pada setiap dekad (Shahid et al, 2017). Semasa tempoh 1969 sehingga 2009, peningkatan suhu permukaan Malaysia direkodkan pada kadar 0.6-1.2°C bagi setiap 50 tahun (NRE, 2011).…”
Section: Implikasi Perubahan Iklim Suhu Permukaanunclassified